Project based STEM activities as an effective educational technology in the context of blended learning - Zavalevskyi, Yurii; Khokhlina, Olena; Gorbenko, Svitlana; Fliarkovska, Olha; Chupryna, Olga (Amazonia Investiga, 2023)
The study aims to investigate the implementation of project-based STEM activities within a blended learning framework in higher education. This approach encourages students' independent creativity and prepares them for contemporary work environments. STEM education is positioned as a tool to develop key competencies like multicultural understanding, linguistic skills, and adaptability. This innovative educational method emphasizes the real-world application of scientific, mathematical, technical, and engineering knowledge. The research methodology combines theoretical analysis with practical evaluation. Key findings underscore the significance of independent research, interdisciplinary integration, and skill development in a blended learning environment. A notable outcome emphasizes empowering students to craft scalable business models, such as startups, vital for success in today's world.